2002
DOI: 10.1152/ajpregu.00736.2001
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional nutrition programs development of the cardiovascular system in the fetal sheep

Abstract: -It has been proposed that fetal adaptations to intrauterine nutrient deprivation permanently reprogram the cardiovascular system. We investigated the impact of restricted periconceptional nutrition and/or restricted gestational nutrition on fetal arterial blood pressure (BP), heart rate, rate pressure product, and the fetal BP responses to ANG II and the angiotensin-converting enzyme inhibitor captopril during late gestation. Restricted periconceptional nutrition resulted in an increase in fetal mean arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
63
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 35 publications
6
63
0
1
Order By: Relevance
“…pregnancy; nutrition; fetus; epigenetic IT HAS BEEN DEMONSTRATED in a range of epidemiological and experimental studies that exposure of the oocyte, embryo, or fetus to a range of environmental stressors, including poor maternal nutrition, results in poor metabolic and cardiovascular outcomes in postnatal life (8,9,13,22,25,41,42,53,56). In sheep, maternal undernutrition from 60 days before to 30 days after conception resulted in an impairment of the insulin and glucose responses to a glucose tolerance test at 10 mo after birth (49).…”
mentioning
confidence: 99%
“…pregnancy; nutrition; fetus; epigenetic IT HAS BEEN DEMONSTRATED in a range of epidemiological and experimental studies that exposure of the oocyte, embryo, or fetus to a range of environmental stressors, including poor maternal nutrition, results in poor metabolic and cardiovascular outcomes in postnatal life (8,9,13,22,25,41,42,53,56). In sheep, maternal undernutrition from 60 days before to 30 days after conception resulted in an impairment of the insulin and glucose responses to a glucose tolerance test at 10 mo after birth (49).…”
mentioning
confidence: 99%
“…Fetuses of ewes undernourished (UN) before until 7 d after mating also showed altered development of the HPA axis (21) and altered fetoplacental growth (22). Late gestation twin fetuses of ewes UN only during the preattachment period (days 0 -7) had altered regulation of blood pressure (23). We have shown that maternal undernutrition from 61 d before until 30 d after mating resulted in extensive changes in the late gestation fetus, including altered regulation of fetal growth (6,24) and the fetal somatotrophic axis (25), changes in placental function, and accelerated maturation of the HPA axis (26) resulting in preterm birth (27).…”
mentioning
confidence: 99%
“…The data are primarily derived from either rodent (see Watkins et al (2008aWatkins et al ( ,b, 2010) or sheep models (Edwards & McMillen (2002), , 2010, Todd et al 2009, Lie et al 2013, Nicholas et al 2013. As shown in the Table 1, the timing of the periconceptional insult may include oocyte maturation and the preimplantation period.…”
Section: Animal Models Of Periconceptional Exposurementioning
confidence: 99%
“…Using a maternal diet containing 70% of required energy from 6 weeks before mating until day 7 of pregnancy, late gestation twin fetuses had increased blood pressure (Edwards & McMillen 2002). Kidneys of undernourished fetuses were of a similar weight to control at day 50 of pregnancy, though they exhibited increased expression of renal IGF1 and HSD11B2 mRNA but decreased IGF1R mRNA expression , suggesting that renal development may be affected.…”
Section: Sheep Modelsmentioning
confidence: 99%